2018
DOI: 10.1007/s00408-018-0098-6
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hemodynamic Assessment by a Novel Index in Systemic Sclerosis Patients: Pulmonary Pulse Transit Time

Abstract: pPTT was found to be shorter in SSc patients. pPTT might serve as a surrogate marker of pulmonary hemodynamics in patients with SSc, even prior to the development of pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…PAS and other abnormal ow hemodynamics in PAH are strongly associated with impaired elevated right ventricular functions and also with disease severity and poor clinical outcomes in patients with PAH [23]. [32]. Consistent with this, we revealed that PAS increased in SSc patients compared to healthy volunteers, and we also determined a positive correlation between Scl duration and PAS.…”
Section: Discussionsupporting
confidence: 88%
“…PAS and other abnormal ow hemodynamics in PAH are strongly associated with impaired elevated right ventricular functions and also with disease severity and poor clinical outcomes in patients with PAH [23]. [32]. Consistent with this, we revealed that PAS increased in SSc patients compared to healthy volunteers, and we also determined a positive correlation between Scl duration and PAS.…”
Section: Discussionsupporting
confidence: 88%
“…In another study, pPTT was significantly shorter in PHT than without pulmonary fibrosis . It has been shown that pPTT is shortened and inversely correlated with disease severity and duration in patients with scleroderma and systemic lupus erythematosus, which cause increased pulmonary arterial stiffness . In the aforementioned studies, pulmonary arterial hemodynamics was assessed with pPTT in patients with precapillary PHT.…”
Section: Discussionmentioning
confidence: 99%
“…Research's on PPTT continued after the study by Wibmer et al Doan et al found that PPTT may be the first sign of early abnormalities of pulmonary hemodynamics in individuals with systemic sclerosis (SSc) 14 . In a study of HIV‐positive patients, PPTT has been shown to indicate the potential presence of pulmonary vascular disease, even though sPAP is within the normal range 15 .…”
Section: Discussionmentioning
confidence: 99%